IMPLIKASI KHATM KHWAJIGAN PADA KESALEHAN SOSIAL BAGI PENGIKUT TAREKAT QADIRIYYAH WA NAQSYABANDIYYAH DUSUN PESALAKAN BANDAR BATANG - Nasirin, Muhammad; Muzakki, Ahmad (At-Turost : Journal of Islamic Studies, 2022)
This research is motivated by the decline in social aspects in the order of social life. In this era of globalization, people are increasingly showing apathy towards the values of social solidarity. This is characterized by an individualistic life style and acting as they please, only using their personal ego without carring about their empathy for other. The tarekat Qodiriyyah wa Naqsabandiyyah through its Khatm Khawajigan provides a formulation for followers to always prioritize character and morality. Tarekat believed to be a Sufi organization capable of growing and reflecting moral and social values in life. By looking at the background of the problem that the author put forward, several formulations of the problem arise. First, what is the practice taught in Khatm Khawajigan?, Second, how does Khatm Khawajigan’s activities affect social piety in society? This study uses a direct field observation methodology (field research). The purpose of this study is to describe the implications of Khatm Kwajigan’s activities on social piety for followers of the Tarekat in Dusun Pesalakan. The method used this cresearch descriptive analytical method, using social approach. The subjects in this study were the congregation who participated in Khatm Khawajigan activities using purposive sampling. Meanwhile, the validity of the data was tasted through triangulation techniques. The results of this study indicate that: (1) In the Khatm Khawajigan’s activity, a lot of dzikir reading are read, besides that there is a lavy for charity jariyah and it is closed with mauidzatul hasanah. (2) In its implication, Khatm Khawajigan’s activities on Social Piety for followers of the Qadriyyah wa Naqsabandiyyah Tarekat in Hamlet Pesalakan can be seen from several Indications, caring for others, creating household hamony, maintaining ukhuwah, and helping each other.